2023
DOI: 10.1155/2023/1214430
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Carbon Nanofoam Targets for Laser-Driven Inertial Fusion Experiments

A. Maffini,
M. Cipriani,
D. Orecchia
et al.

Abstract: Porous materials have peculiar characteristics that are relevant for inertial confinement fusion (ICF). Among them, chemically produced foams are proved to be able to smooth the laser inhomogeneities and to increase the coupling of the laser with the target. Foams realized with other elements and techniques may prove useful as well for ICF applications. In this work, we explore the potential of a novel class of porous materials for ICF, namely, carbon nanofoams produced with the pulsed laser deposition (PLD) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our previous works we also performed a quantitative analysis of the nanofoams uniformity features, aided by energy-dispersive X-spectroscopy (EDXS) maps and a method based on their Fourier transform. [26,51,56] Due to the different properties of the materials investigated in this work (higher-Z elements together with higher density and film thickness), the same approach would not be feasible. Moreover, in our previous works, we showed that the results of the EDXS maps' investigation were in agreement with the qualitative analysis of the nanofoam morphology through SEM micrographs, which is already rich in information and therefore has been chosen as the focus of this investigation.…”
Section: Morphological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works we also performed a quantitative analysis of the nanofoams uniformity features, aided by energy-dispersive X-spectroscopy (EDXS) maps and a method based on their Fourier transform. [26,51,56] Due to the different properties of the materials investigated in this work (higher-Z elements together with higher density and film thickness), the same approach would not be feasible. Moreover, in our previous works, we showed that the results of the EDXS maps' investigation were in agreement with the qualitative analysis of the nanofoam morphology through SEM micrographs, which is already rich in information and therefore has been chosen as the focus of this investigation.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…[15,16] In the past years, nanofoams have been studied as effective enhancers in high-intensity laser-matter interaction [17] for laser-driven ion acceleration, [18][19][20][21] neutron [22] and radioisotopes generation, [23] and inertial confinement fusion. [24][25][26] Moreover, nanofoams can serve as model materials for fundamental nanotechnology research. Scientists study their unique properties and behavior to gain insights into nanoscale phenomena, which can lead to further advancements in materials science.…”
Section: Introductionmentioning
confidence: 99%